Analysis of Fatty Acid Composition Using GC-MS and Antibacterial Activity Test of n-Hexane Extract from Jengkol Seeds (Pithecellobium lobatum Benth.) - Marpaung, Lamek; Siahaan, Surya Graha P. (Journal of Chemical Natural Resources, 2023)
Analysis of fatty acid composition using GC-MS and antibacterial activity test of n-hexane extract from Jengkol seeds (Pithecellobium lobatum Benth) was performed with the maceration method to obtain n-hexane extract of Jengkol seeds. The n-hexane extract of Jengkol seeds was first esterified using methanol (1.7 ml): 98% H2SO4 (0.3 ml): Chloroform (2 ml), then analyzed its fatty acid composition by GC-MS method. The results of fatty acid composition analysis found in Jengkol seeds are saturated fatty acids, namely: Margaric Acid (1.10%), Palmitate Acid (2.64%), stearic acid (12.01%), and unsaturated fatty acids, namely: Linolelaidate acid (10.02%) %), and oleic acid (74.23%). The antibacterial activity test against Escherichia coli and Staphylococcus aureus using n-hexane extract of Jengkol seed was done by agar diffusion method. The concentration variations were 50 mg/ml, 150 mg/ml, and 250 mg/ml. From the results of this test, n-hexane Jengkol seeds have an antibacterial activity that can inhibit bacterial growth but is weak (â‰¤14 mm).